General and specific responses of understory vegetation to cervid herbivory across a range of boreal forests. Issue 10 (13th May 2014) - Speed, James D. M.; Austrheim, Gunnar; Hester, Alison J.; Meisingset, Erling L.; Mysterud, Atle; Tremblay, Jean‐Pierre; Øien, Dag‐Inge; Solberg, Erling J.
<x xml:space="preserve">Abstract</x> Understanding the responses of ecological communities to perturbation is a key challenge within contemporary ecology research. In this study we seek to separate specific community responses from general community responses of plant communities to exclusion of large cervid herbivores. Cervid herbivory and forestry are the main drivers of vegetation structure and diversity in boreal forests. While many studies focus on the impact of cervids on trees, a high proportion of the biodiversity and ecosystem services in boreal forests is found in the field layer. However, experimental approaches investigating the influence of herbivory on understory vegetation are highly localised. In this study we use a regional‐scale design with 51 sites in four boreal forest regions of Norway, to investigate the influence of cervid herbivory on the physical and ecological structure of field layer vegetation. Our study sites cover a range of forest types differing in productivity, management and dominant cervid species, allowing us to identify generic responses and those that are specific to particular conditions. We found that the height of the field layer and the abundances of individual species were most susceptible to change following short‐term cervid exclusion across different forest types and cervid species. Total vegetation density and vascular plant diversity did not respond to cervid exclusion on the same time scale. We also found that the field‐layer vegetation in clear‐cut forests used by moose was more susceptible to change following cervid exclusion than mature forests used by red deer, but no strong evidence that the response of vegetation to herbivore exclusion varied with productivity. Our study suggests that the parameters that respond to cervid exclusion are consistent across forest types, but that the responsiveness of different forest types is idiosyncratic and hard to predict.